2013
DOI: 10.4304/tpls.3.9.1572-1578
|View full text |Cite
|
Sign up to set email alerts
|

EFL Instructors and Student Writers’ Perceptions on Academic Writing Reluctance

Abstract: Students' disengagement in class activities is usually interpreted from the instructors' viewpoints, disregarding students' perceived causes of the phenomenon. This study investigated instructors and students' perceptions on writing reluctance, aiming at exploring possible convergence and divergence between the participants' ideas. Twelve instructors and thirty seven students completed a questionnaire developed by the researchers. It includes linguistic factors (e.g. task difficulty, linguistic competence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Moreover, they are not interested in the topics. As Asadifard and Koosha (2013) suggest, the results also suggest and support that they are not willing to write due to their prior negative experiences with writing tasks; thus, they need encouragement provided by the teacher since they reported that they feel a lack of appropriate interpersonal relationships between their teacher and themselves. Thus, they believe they do not have adequate writing activities to encourage them to write.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, they are not interested in the topics. As Asadifard and Koosha (2013) suggest, the results also suggest and support that they are not willing to write due to their prior negative experiences with writing tasks; thus, they need encouragement provided by the teacher since they reported that they feel a lack of appropriate interpersonal relationships between their teacher and themselves. Thus, they believe they do not have adequate writing activities to encourage them to write.…”
Section: Resultsmentioning
confidence: 59%
“…Lastly, these items may be misinterpreted by students in various ways depending on their contexts. Asadifard and Koosha (2013) found that there is a high degree of reluctance among students towards writing activities; they are perhaps among their last choices, or they try not to engage themselves in writing unless they have to. Also, they stated that when the students feel their works may not be thoroughly checked, they gradually lose their interest in writing hence reluctance may be the outcome.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same vein, another study on EFL instructors and student writers' perceptions on academic writing reluctance, in an Iranian context, by Asadifard and Koosha (2013) reports striking results as well. The study reports firstly on the mismatch between instructor and student writer perceptions regarding task difficulty that 100% of the instructors declared that reluctance depends on task difficulty while the 16% of the students agreed with the instructors, and some 54% students stated reasons other than task difficulty for reluctance.…”
Section: The Writer As a Major Variable In Efl Writingmentioning
confidence: 86%
“…Most interestingly, Asadifard and Koosha (2013) find that learners and instructors may have different perceptions concerning the factors causing lack of engagement in writing activities initiated by the instructor. This perception difference is possible to become the main reason behind students' disengagement as well as the unnoticed blind spot when instructors design the pedagogical approach for the writing class.…”
Section: Introductionmentioning
confidence: 95%
“…To highlight it once again, scholars who researched on writing reluctance (e.g., Asadifard & Koosha, 2013;Meiketo & Tessema, 2012) have agreed that there is a strong indication where instructors and students perceive factors which cause disengagement differently. Instructors tend to believe that the cause of disengagement merely is because students are not well prepared to engage and they lack the prerequisite skills that could enable them to engage.…”
Section: Students' Writing Reluctance and Instructor-initiated Writinmentioning
confidence: 99%